One-pot extractive and oxidative desulfurization of fuel with ternary dual-acid deep eutectic solvent. (1st December 2022) - Jin, Dongyu; Yu, Guojia; Li, Xinyu; Li, Tenghui; Zhang, Fan; Tian, Shichao; Zhou, Zhiyong; Ren, Zhongqi
Graphical abstract: Highlights: Novel dual-acid DESs were prepared with L-Pyro acid and PEG as HBA and TsOH as HBD. One-pot extractive and oxidative desulfurization process was proposed. The desulfurization efficiencies of DBT and 4, 6-DMDBT reached 100% and 96.54%. The ODS process conformed to the first-order reaction kinetics model. The synthesized DES in this work showed good chemical stability and reusability. Abstract: A series of ternary dual-acid deep eutectic solvents were prepared using L-Pyroglutamic acid (L-Pyro) and low-viscosity polyethylene glycol (PEG) as hydrogen bond acceptors and p -toluenesulfonic acid (TsOH) as hydrogen bond donors. The effects of acidity and viscosity on extractive and oxidative desulfurization performances (H2 O2 as oxidant) were investigated. Among them, L-Pyro/2TsOH/2PEG200 was selected as the target deep eutectic solvent owing to its excellent removal performance for aromatic sulfur compounds. The successful synthesis of DES was confirmed by FTIR spectroscopy and H NMR. Under the optimal reaction conditions, the desulfurization efficiencies of dibenzothiophene and 4, 6-dimethyldibenzothiophene reached up to 100 % and 96.54 % within 3 h, respectively. The desulfurization efficiency of the deep eutectic solvent regenerated with a small amount of ultrapure water remained constant in six reused cycles, indicating that deep eutectic solvent had good stability and reusability. Finally, the results of free radical burst experiments demonstrated the existence of superoxide radicals and hydroxyl radicals, and the desulfurization mechanism was proposed. This research provides a novel strategy for deep desulfurization of fuel.